Climate change and commercial fishing practices codetermine survival of a long‐lived seabird. Issue 2 (22nd October 2022) - Gibson, Daniel; Riecke, Thomas V.; Catlin, Daniel H.; Hunt, Kelsi L.; Weithman, Chelsea E.; Koons, David N.; Karpanty, Sarah M.; Fraser, James D.
Abstract: Understanding the environmental mechanisms that govern population change is a fundamental objective in ecology. Although the determination of how top‐down and bottom‐up drivers affect demography is important, it is often equally critical to understand the extent to which, environmental conditions that underpin these drivers fluctuate across time. For example, associations between climate and both food availability and predation risk may suggest the presence of trophic interactions that may influence inferences made from patterns in ecological data. Analytical tools have been developed to account for these correlations, while providing opportunities to ask novel questions regarding how populations change across space and time. Here, we combine two modeling disciplines—path analysis and mark‐recapture‐recovery models—to explore whether shifts in sea‐surface temperatures (SSTs) influenced top‐down (entanglement in fishing equipment) or bottom‐up (forage fish production) population constraints over 60 years, and the extent to which these covarying processes shaped the survival of a long‐lived seabird, the Royal tern. We found that hemispheric trends in SST were associated with variation in the amount of fish harvested along the Atlantic coast of North America and in the Caribbean, whereas reductions in forage fish production were mostly driven by shifts in the amount of fish harvested by commercial fisheries throughout the North Atlantic the year prior. Although the indirect (i.e., stock depletion) and direct (i.e., entanglement) impacts of commercial fishing on Royal tern mortality has declined over the last 60 years, increased SSTs during this time period has resulted in a comparable increase in mortality risk, which disproportionately impacted the survival of the youngest age‐classes of Royal terns. Given climate projections for the North Atlantic, our results indicate that threats to Royal tern population persistence in the Mid‐Atlantic will most likely be driven by failures to recruit juveniles into the breeding population. Abstract : Commercial fishing intensity (a) was directly (via entanglement risk associated with long‐line fishing) and indirectly (via reductions in Atlantic menhaden production associated with commercial trawling) link to increased risk of Royal tern mortality. Although (b) sub‐adult (ages 3–4) and adult (age >5) survival has increased over time partially as a function of reductions in pressures related to commercial fishing, survival of the youngest age‐class of Royal terns was primarily associated with increased sea‐surface temperatures in the North Atlantic.